Evaluation of Economic Approaches for the Development of Liberalism: A Theoretical Analysis - Asfore Lafta, Abaas; Makki Hamzah, Abbas; Ibrahim Mahdi Alzurfi, Ahmed; M. Jawad AL.Musawi, Abdulwahab (International Journal of Psychosocial Rehabilitation, 2020)
International economic drama resulted from the emergence of neoliberalism with radical changes to the theses of capitalism. This approach is a direct result of the increasing challenges that brought down many capital constants, after which globalization came to face financial crises as well as the collapse of some major institutions and banks. The paper aims to explore the most important intellectual contributions that led to the maturity of contemporary liberal thought. Moreover, the paper aims to uncover how the gradual consolidation of economic features today and its impact on changing the economic features of societies.